TOMAS LIDMAN, Libraries and Archives: A Comparative Study - Harvey, Kathryn (Archivaria, 2013)
Libraries and Archives: A Comparative Study. TOMAS LIDMAN. Oxford: Chandos Publishing, 2012. xvi, 123 pp. ISBN 978-1-84334-642-5.